Concentración mínima inhibitoria de gentamicina frente a Escharichia coli en muestras de urocultivo de pacientes de consulta externa del Hospital Militar de la ciudad de Loja - Chimbo Torres, Ángel Eduardo (2015)
American trypanosomiasis, known as Chagas disease, is a chronic zoonosis vector in immunocompetent; and opportunistic in immunocompromised. Given this disease presents its evolution towards chronicity and goes through three stages: acute, indeterminate and chronic (1). This research purposes titration called "Identification of antibodies against Trypanosoma cruzi and risk factors for transmission vector of the neighborhood residents 'extensive' canton Catamayo" the general aim of identifying antibodies to Trypanosoma cruzi and raised Risk factors for transmission vector residents of the neighborhood "extensive" canton Catamayo, in the period February-March 2013 and the following specific objectives: To detect antibodies to Trypanosoma cruzi by ELISA to the residents of Barrio "extensive" Canton Catamayo; Identify risk factors influencing the spread of intra domiciliary and peridomiciliary triatomine vectors; Statistically determine the association between Trypanosoma cruzi antibodies and risk factors of vector-borne; and disseminate the results, the community and the medical staff of the Health Center of Catamayo. This is a descriptive study, of cross section. In the first instance the inclusion and exclusion criteria were established and a sample of 123 individuals was selected. To collect data on risk factors survey was applied and for the determination of serum antibody ELISA was used. It was determined that a person presented high DO two standard deviations above the controls for IgG, which corresponds to 0.8% of the sample. The most common risk factors were tiled roof in 90% of cases, floor in 55% of cases, adobe walls in 28% of cases and mixed construction walls in 24% of cases. Preventive action to avoid getting bitten by triatomine was the use of the awning to sleep in 69% of cases. Finally, no significant statistical relationship between serum antibodies and risk factors of vector transmission was established. Keywords: Trypanosoma cruzi, antibodies, Vector, Triatomines.